Epidemiological profile of HIV/AIDS in Brazil based on data from DataSUS in the year 2021 (Research, Society and Development, 2022)
Introduction: HIV/AIDS is an infectious disease that affects the CD4 T cells, the defense of the human body. Methodology: The present epidemiological profile of HIV/AIDS developed in this study is a cross-sectional study, in which the present researchers observed the data collected and saved from the DataSUS and SINAN programs. Results: We observed that in 2021 there were 13,501 new cases of HIV/AIDS in Brazil, of which 71.8% were male (n=9,705), 28.6% (n=3,789) of females; the population adept of Heterosexual sexuality registered a percentage of 18.7% (n= 2,536), in second place the homosexuals with about 10.5% (n= 1,423) for HIV/AIDS; ages 40 to 59 years old with a percentage of 21.6% (n= 2,923), 25 to 29 years old reported 17.4% (n= 2,350) and 30 to 34 years old, with a percentage of 15.1% (n= 2,045); the Southeast Region, with 37.2% (n= 5,032), the Northeast, with 22% (n= 2,982), and the South Region, accounting for 17.7% (n= 2,401) of the reported cases; The states of São Paulo, Rio de Janeiro and Rio Grande do Sul reported the highest cases of the disease, in which, respectively, their percentages of contagion were: 18.3% (n= 2,484), 10.4% (n= 1,414 ) and 7.9% (n=1067). Conclusion: We observed that males were the most affected, due to the high rate of underreporting in the exposure category, it was impossible to reveal the highest incidence rate of the virus in this variable. Confirmed cases in the age group of 60 years and over worry public health authorities and warn of a possible “aging epidemic”.